Does obesity affect the outcomes in takotsubo cardiomyopathy? Analysis of the Nationwide Inpatient Sample database, 2010‐2014. Issue 8 (17th August 2018) - Desai, Rupak; Singh, Sandeep; Baikpour, Maryam; Goyal, Hemant; Dhoble, Abhijeet; Deshmukh, Abhishek; Kumar, Gautam; Sachdeva, Rajesh
Abstract : Background: Obesity can lead to increased oxidative stress which is one of the proposed mechanisms in the etiopathogenesis of takotsubo cardiomyopathy (TCM). Hypothesis: The presence of obesity adversely impacts clinical outcomes in TCM patients. Methods: We queried the Nationwide Inpatient Sample database (2010‐2014) to identify adult patients admitted with a principal diagnosis of TCM with and without obesity. We compared the categorical and continuous variables by Pearson χ 2 and Student t test, respectively, in propensity‐score matched cohorts. Results: The study cohort comprised 612 obese TCM (weighted n = 3034) and 5696 nonobese TCM (weighted n = 28 186) patients. Obese TCM patients were more often younger and private‐insurance enrollees. Cardiac complications including acute myocardial infarction (9.0% vs 7.4%; P = 0.04), cardiac arrest (2.3% vs. 0.4%; P < 0.001), cardiogenic shock (4.3% vs. 3.2%; P = 0.03), congestive heart failure (5.0% vs. 3.8%; P = 0.02), respiratory failure (12.9% vs. 11.0%; P = 0.021) and use of mechanical hemodynamic support (Impella; 0.2% vs. 0.0%, P = 0.02) were significantly higher among obese TCM patients. There were no significant differences between the 2 groups in all‐cause mortality (1.0% vs. 0.8%; P = 0.35), arrhythmia (24.5% vs. 22.7%, P = 0.123), length of stay (3.7 ±3.5 vs. 3.7 ±3.6 days; P = 0.68), and total hospital charges ($40 780.16 vs. $42 575.14; P = 0.08). Conclusions: Obese TCM patients were more susceptible to developing TCM‐related cardiac complications than were nonobese TCM patients, without any impact on all‐cause in‐hospital mortality, LOS, and hospital charges.